Caso hematológico: Esferocitose hereditária - Costa, M (2014)
Aplastic crisis by Parvovirus B19 in a patient with hereditary spherocytosis can produce an acute severe and eventually life-threatening anemia. The authors present a clinical case of a 14-year old boy, enhancing the importance of clinical evaluation for a prompt diagnosis and therapeutic approach.